Preparation and characterization of poly(vinyl alcohol)/halloysite nanotubes composite sponges with improved mechanical properties. Issue 7 (28th March 2021) - Chen, Tianxiang; Chen, Sina; Wang, Jinyun; Lin, Tengfei; Wu, Weihang; Yang, Weijin; Wang, Yu
Abstract: A novel polyvinyl alcohol (PVA)/halloysite nanotubes (HNTs) composite sponge with preferable properties was fabricated via water solution mixing and casting technique with a fixed PVA ratio and the various contents of nano‐fillers. The morphology and physical properties of all the samples have been studied and characterized extensively. The results showed that HNTs were uniformly aligned along in the PVA matrix depending on good interfacial interactions between HNTs and PVA matrix. The addition of HNTs decreased the pore sizes and porosity of the sponges. Mechanical tests indicated that the incorporation of HNTs contribute to the reinforcement in mechanical properties of composite sponges under both dry and moist conditions. In addition, the composites showed better performances in thermal stability and water absorption capacity than pure PVA sponges. Rhodamine B and ibuprofen were employed to evaluate the control release ability. The results illustrated that increasing HNT contents can enhance the sustained release ability of PVA sponges. Abstract :